When x2 - 5x + p is divided by (x - 2), the remainder is 3. Then the value of p is :
9
-9
-6
6
3 Likes
By remainder theorem,
If a polynomial p(x) is divided by (x - a), then remainder = p(a).
⇒ x - 2 = 0
⇒ x = 2.
Given,
On dividing x2 - 5x + p by (x - 2), remainder = 3.
∴ 22 - 5(2) + p = 3
⇒ 4 - 10 + p = 3
⇒ p - 6 = 3
⇒ p = 3 + 6 = 9.
Hence, Option 1 is the correct option.
Answered By
2 Likes
20 identical articles are sold at ₹ 350 each with GST = 12%. 10 other type of articles are sold at ₹ 500 each with GST = 18%. Total amount of bill is :
₹ 12000
₹ 13440
₹ 13740
₹ 14160
Which term of the A.P. 30, 27, 24, 21, ….. is the first negative term ?
10th
11th
14th
12th